Magnitude of depression and its determinants among older persons in urban community of Agra - Singh, Anshumali; Kaushal, Suneel Kumar; Misra, Sunil Kumar; Agrawal, Renu; Sinha, Vishal (Indian Journal of Community Health, 2018)
Background: With increasing life expectancy people are living longer but they are not necessarily healthier than before. Nearly a quarter (23%) of the overall global burden of death and illness is in people aged over 60, and much of this burden is attributable to long-term illness like non-communicable diseases and mental health problems. Aims & Objectives: Aim of the study the magnitude of depression among elderly population of Agra. Objectives To estimate the prevalence of depression in elderly population of Agra. 2. To study the factors associated with depression among elderly population of Agra. Material and Methods: This study was conducted among 355 elderly in urban Agra. Data was collected by house to house visit using pre-designed and pre-tested schedule. Geriatric depression scale (GDS-30) was used to assess the burden of depression in study population. Results: The mean age of the study participants was 68.05 years. Depression was found in 50.1% among study population and 15.5% had severe depression. Depression was more among the Illiterates, Muslims, financial dependents, those who were suffering from chronic disease/s, encountered a stressor in the last 6 months, less religious, not living with partner or suffered elderly abuse. Conclusion: High burden of depression was found among the victims of elderly abuse. Stressful life events and absence of spouse were found to be significant risk factors for depression. To deal with these factors we suggest a link worker Geriatric Age Social Health Agent (G-ASHA) to act as a link between family, community and authorities.